Biomedical researchers’ perspectives on the reproducibility of research - Cobey, Kelly D.; Ebrahimzadeh, Sanam; Page, Matthew J.; Thibault, Robert T.; Nguyen, Phi-Yen; Abu-Dalfa, Farah; Moher, David (PLOS Biology, 2024)
We conducted an international cross-sectional survey of biomedical researchers’ perspectives on the reproducibility of research. This study builds on a widely cited 2016 survey on reproducibility and provides a biomedical-specific and contemporary perspective on reproducibility. To sample the community, we randomly selected 400 journals indexed in MEDLINE, from which we extracted the author names and emails from all articles published between October 1, 2020 and October 1, 2021. We invited participants to complete an anonymous online survey which collected basic demographic information, perceptions about a reproducibility crisis, perceived causes of irreproducibility of research results, experience conducting reproducibility studies, and knowledge of funding and training for research on reproducibility. A total of 1,924 participants accessed our survey, of which 1,630 provided useable responses (response rate 7% of 23,234). Key findings include that 72% of participants agreed there was a reproducibility crisis in biomedicine, with 27% of participants indicating the crisis was “significant.” The leading perceived cause of irreproducibility was a “pressure to publish” with 62% of participants indicating it “always” or “very often” contributes. About half of the participants (54%) had run a replication of their own previously published study while slightly more (57%) had run a replication of another researcher’s study. Just 16% of participants indicated their institution had established procedures to enhance the reproducibility of biomedical research and 67% felt their institution valued new research over replication studies. Participants also reported few opportunities to obtain funding to attempt to reproduce a study and 83% perceived it would be harder to do so than to get funding to do a novel study. Our results may be used to guide training and interventions to improve research reproducibility and to monitor rates of reproducibility over time. The findings are also relevant to policy makers and academic leadership looking to create incentives and research cultures that support reproducibility and value research quality.